Measurement of distributions sensitive to the underlying event in inclusive Z-boson production in [Formula: see text] collisions at [Formula: see text] TeV with the ATLAS detector. - Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; et al. (2014)
A measurement of charged-particle distributions sensitive to the properties of the underlying event is presented for an inclusive sample of events containing a [Formula: see text]-boson, decaying to an electron or muon pair. The measurement is based on data collected using the ATLAS detector at the LHC in proton-proton collisions at a centre-of-mass energy of [Formula: see text] TeV with an integrated luminosity of [Formula: see text] fb[Formula: see text]. Distributions of the charged particle multiplicity and of the charged particle transverse momentum are measured in regions of azimuthal angle defined with respect to the [Formula: see text]-boson direction. The measured distributions are compared to similar distributions measured in jet events, and to the predictions of various Monte Carlo generators implementing different underlying event models.